Non-Circular Hydraulic Jump on a Moving Surface due to an Impinging Circular Free Surface Jet of Water - Seraj, Mohammad M.; Gadala, Mohamed S. (Steel research international, 2012)
Liquid jet impingement has many industrial cooling applications such as metal manufacturing and steel cooling on run‐out tables (ROT). The development of the wetting front around the impingement point of a jet is central in jet impingement cooling. In this paper, the effects of moving target surface and jet Reynolds number on wetted zone and on the formation and location of hydraulic jump (HJ) are explored through a series of industrial‐scale experiments of an impinging circular free surface long water jet with high Reynolds number of 11 000–50 000 and industrial jet parameters. The moving test surface impacts the radial evolution of circular wetted zone in all directions and alter the circular HJ at the wetting front into a non‐circular contour that depends on the jet Re number. The limited relations in the literature do not represent these measured shapes and do not appropriately predict radii of HJ in industrial scale. A new correlation for radius of non‐circular HJ has been derived in this study that compared more accurately to the experimental data. Numerical simulations of radial impingement flow on moving surface were performed using a variant of k–ε turbulent model and results are compared to the experimental data. The computational results for the wetting front were found to be close to the experimental data indicating the appropriate performance of the turbulent model. This paper reports results of experimental and numerical investigations on spreading of wetting front over a moving impingement surface due to a water jet with industrial parameters. The jet flow rate and speed of moving surface were found influential parameters in shaping and sizing the wetted zone. The correlations for radii of wetting front were proposed covering all data with ±7% error.